Peranan Gereja dari Kisah Para Rasul 4:28–29 terhadap Pengabaran Injil kepada Orang yang Belum Percaya di GEKI MRC Medan Marelan - Fitrianus Telambenua; Tirsanika Surbakti; Lisbet Parulian; Elda Buana Gurning; Joel Nababan; David Mariepan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The church has the responsibility to fulfill the Great Commission through evangelistic ministry that is responsive to the needs of society. However, the implementation of evangelistic mission faces various challenges that require churches to develop contextual ministry strategies while actively involving the entire congregation. This study aims to describe the role of GEKI MRC Medan Marelan Church in carrying out its evangelistic mission and to identify the forms of ministry that support the implementation of this mission. The study employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. The research participants consisted of church members, cell group leaders, and church ministry leaders. The findings reveal that GEKI MRC Medan Marelan Church plays an active role in conducting various evangelistic activities, including seminars, Bible study, social outreach, pastoral home visits, and community-based programs involving local residents. These activities encourage congregational participation in ministry while expanding the reach of the Gospel through relational and contextual approaches. The findings also indicate that the active involvement of church members strengthens the relationship between the church and the community and enhances the effectiveness of evangelistic ministry. The study implies that churches should continue to develop innovative, participatory, and adaptive evangelistic strategies in response to social changes so that evangelistic ministry remains relevant and generates a positive impact on both the congregation and the wider community.